d uthor, Charles Broto i Comerma ; text, Monica Camacho ; illustrations, Pilar Chueca, Dimitris Kottas.h - Broto, Carles. 4 0 16; Camacho, Monica.;Kottas, Dimitris,;Chueca, Pilar; 5 (Singapore : Page One)
Wondering what an ogee molding is? Puzzling over flying buttresses? This book shows and tells these words and thousands more. More than 6000 architectural terms are explained in over 500 detailed illustrations plus captions in English, Spanish, French and German.
Includes index.
Keywords: 2 -- 0; 6; Dictionaries.;Dictionaries. -- Architecture;Building; 20; 2